Corporate Governance, Financial Ratio and Real Earnings Management in Indonesia Stock Exchange - Maharani Dwi Nastiti; Yulis Kurnia Susanto (Faculty of Economics, Universitas Internasional Batam, 2022)
Purpose - The goal of this study is to gather empirical information on the impact of audit quality, board of directors, independent commissioners, managerial ownership, institutional ownership, profitability, firm leverage, firm size, and firm age on earnings management. Research Method - The demographic for this study was non-financial companies that were listed on the Indonesia Stock Exchange between 2018 and 2020. This study examined a sample of 148 listed non-financial companies. Purposive sampling was utilized in the sample methodology, and multiple regression was used to evaluate the data. Findings - Board of directors, independent commissioners, institutional ownership, and profitability have an impact on real earnings management. While, audit quality, managerial ownership, firm leverage, firm size, and firm age have no impact on real earnings management. Implication - Increased profitability signals good firm performance, and shareholders will benefit as well. Furthermore, managers will benefit as well if company performance improves, thus managers are not driven to adopt earnings management initiatives.